1995
DOI: 10.1101/gad.9.12.1505
|View full text |Cite
|
Sign up to set email alerts
|

c-Src enhances the spreading of src-/- fibroblasts on fibronectin by a kinase-independent mechanism.

Abstract: We have explored the role of the tyrosine kinase c-Src in cellular adhesion. Fibroblasts derived from src-~-mice (src-/-fibroblasts) exhibit a reduced rate of spreading on fibronectin. This defect is rescued by expression of wild-type chicken c-Src. Analyses of mutants suggest that c-Src increases the rate of cell spreading in src-/-fibroblasts through a kinase-independent mechanism requiring both the SH3 and SH2 domains. To further address the role of c-Src in adhesion, we examined the activity and subcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
270
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(291 citation statements)
references
References 53 publications
(69 reference statements)
17
270
1
Order By: Relevance
“…Anti-avian Src antibody recognized only exogenous Src protein Oncogene Dominant negative Src inhibits bioactivity of M1268T MET N Nakaigawa et al tumors in vivo were dependent, at least in part, on the binding and activation of c-Src. Kaplan et al (1995) focused attention on the seemingly paradoxical e ects of c-Src and v-Src on cellular adhesion. Kaplan et al (1995) found that c-Src positively in¯uenced cellular adhesion, while v-Src resulted in morphogic transformation and an apparent reduction in cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-avian Src antibody recognized only exogenous Src protein Oncogene Dominant negative Src inhibits bioactivity of M1268T MET N Nakaigawa et al tumors in vivo were dependent, at least in part, on the binding and activation of c-Src. Kaplan et al (1995) focused attention on the seemingly paradoxical e ects of c-Src and v-Src on cellular adhesion. Kaplan et al (1995) found that c-Src positively in¯uenced cellular adhesion, while v-Src resulted in morphogic transformation and an apparent reduction in cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan et al (1995) focused attention on the seemingly paradoxical e ects of c-Src and v-Src on cellular adhesion. Kaplan et al (1995) found that c-Src positively in¯uenced cellular adhesion, while v-Src resulted in morphogic transformation and an apparent reduction in cellular adhesion. The authors suggested that di erent levels of kinase activity in the two proteins in focal adhesions might partially explain the paradox.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, signaling from integrin receptors involves Src family kinases, but may not require Src's kinase activity. Upon crosslinking of integrins, Src is transiently activated and is found in a detergent insoluble fraction, enriched in focal adhesions, the sites where integrins help organize cytoskeletal and signaling proteins in response to adhesion (Kaplan et al, 1995). Fibroblasts derived from src7/7 mice exhibit a defect in initial cell spreading (Kaplan et al, 1995), defects in phosphorylation of an adaptor molecule pp130cas (Bockholt and Burridge, 1995;Hamasaki et al, 1996;Vuori et al, 1996) and a 10-fold attenuation of MAPK activation in response to plating on ®bronectin (Schlaepfer et al, 1997), indicating that Src is critical in pathways downstream of integrin crosslinking.…”
Section: Kinase Domainmentioning
confidence: 99%
“…In fact, defects in integrin signaling in src7/7 cells are actually complemented, in part, by kinase-inactive molecules. For example, either a kinase-inactive point mutant of Src or a truncated molecule that removes the entire kinase domain will complement the cell-spreading defect (Kaplan et al, 1995); these molecules will also increase pp130cas phosphorylation in response to ®bronectin (Schlaepfer et al, 1997 and P Schwartzberg, unpublished observations). A truncated Src molecule lacking the kinase domain has also been demonstrated to restore partial activation of MAPK (Mitogen Activated Protein Kinase) in response to plating on ®bronectin (Schlaepfer et al, 1997).…”
Section: Kinase Domainmentioning
confidence: 99%
See 1 more Smart Citation